Pendidikan Etika Bisnis Syariah Di Perguruan Tinggi: Pendekatan Dan Implementasi - Rahman, Abdul; Khairi, Rifqil; Irwan, Yudi (Journal of Sustainable Education, 2024)
This research aims to explore the approach and implementation of sharia business ethics education in higher education. The main focus of this research is to understand how sharia ethical values ​​are applied in curriculum and teaching, as well as their impact on students' understanding and attitudes towards sharia-based business ethics. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with lecturers and students at several universities that offer sharia business ethics education programs. In addition, curriculum document analysis and classroom observations were carried out to get a comprehensive picture of the approach and implementation used. Data analysis techniques involve thematic coding to identify key patterns and themes that emerge from the data. The research results show that sharia business ethics education in universities is implemented through various approaches, including the integration of sharia values ​​in general business courses, special teaching regarding sharia business ethics, and extracurricular activities that support students' practical understanding. This implementation has a positive impact on students' understanding of the importance of ethics in business and increases their awareness of business practices that comply with sharia principles. However, this research also identified several challenges, such as a lack of adequate resources and the need for further training for lecturers in the field of sharia business ethics.